Association Between Concussions and Suicidality in High School Students in the United States - Iverson, Grant L.; Karr, Justin E. (Frontiers in Neurology, 2022)
Importance Prior research has shown a statistically significant association between sustaining a concussion and suicidality in adolescents, but this prior research controlled for relatively few variables predictive of suicidality. Objective To examine whether sustaining a concussion remained a significant predictor of suicidality after controlling for relevant covariates (e.g., sexual abuse/assault, bullying, substance use, depression), hypothesizing that the relationship between concussion and suicidality would become non-significant after controlling for these variables. Design This study involved secondary data analysis of the 2019 Youth Risk Behavior Surveillance (YRBS) System, a national cross-sectional study of adolescents. Analyses were stratified by gender. Setting A national sampling of U.S. high school students. Participants Eleven thousand two hundred sixty-two students in the YRBS database, including 5,483 boys and 5,779 girls. Exposure(s) Participants included in the analyses reported whether, in the last year, they experienced a concussion and/or suicidality. Main Outcomes and Measures The main outcome was suicidality (i.e., ideation, planning, attempt), which was predicted by concussion in an unadjusted analysis and by concussion along with other risk factors in a multivariable analysis. Results The final sample included 11,262 participants with available data on concussion and suicidality in the last year (14–18 years-old; 51.3% girls; 49.0% White). Per unadjusted odds ratios with 95% confidence intervals, there was a relationship between concussion and suicidal ideation [girls: OR = 1.46 (1.24, 1.73); boys: OR = 1.69 (1.41, 2.03)], planning (girls: OR = 1.39 [1.16, 1.66]; boys: OR = 1.76 [1.44, 2.14]), and attempt [girls: OR = 1.70 (1.32, 2.19); boys: OR = 3.13, (2.37, 4.15)]. These relationships became mostly non-significant after controlling for relevant risk factors for suicidality. The adjusted odds ratios showed no relationship between concussion and suicidal ideation [girls: OR = 1.11 (0.86, 1.44); boys: OR = 1.24 (0.92, 1.69)] or planning (girls: OR = 1.07 [0.82, 1.40]; boys: OR = 1.12 [0.82, 1.55]); but a significant relationship with suicide attempts in boys [OR = 1.98 (1.28, 3.04)], but not girls [OR = 1.05 (0.74, 1.49)]. Conclusions and Relevance There was an association between concussion and suicidality in U.S. high school students; however, after controlling for other variables (e.g., depression, sexual abuse/assault, illicit drug use), there was no association between concussion and suicidality aside from a significant relationship between concussion and attempts in boys.